Nondegeneracy of the ground state for nonrelativistic Lee model - Erman, Fatih; Malkoç, Berkin; Turgut, Osman Teoman (AIP Publishing, 2014)
In the present work, we first briefly sketch the construction of the nonrelativistic Lee model on Riemannian manifolds, introduced in our previous works. In this approach, the renormalized resolvent of the system is expressed in terms of a well-defined operator, called the principal operator, so as to obtain a finite formulation. Then, we show that the ground state of the nonrelativistic Lee model on compact Riemannian manifolds is nondegenerate using the explicit expression of the principal operator that we obtained. This is achieved by combining heat kernel methods with positivity improving semi-group approach and then applying these tools directly to the principal operator, rather than the Hamiltonian, without using cut-offs.
Keywords: Hilbert space; Nuclear physics; FOS: Physical sciences; Eigenvalues; Mathematical Physics (math-ph); Ground states; Riemannian manifolds; Lee model; Field theory; Spectrum, resolvent; Mathematical Physics; Heat kernel